Tissue Engineered Bands of Büngner for Accelerated Motor and Sensory Axonal Outgrowth - Panzer, Kate V.; Burrell, Justin C.; Helm, Kaila V. T.; Purvis, Erin M.; Zhang, Qunzhou; Le, Anh D.; O’Donnell, John C.; Cullen, D. Kacy (Frontiers in Bioengineering and Biotechnology, 2020)
Following peripheral nerve injury comprising a segmental defect, the extent of axon regeneration decreases precipitously with increasing gap length. Schwann cells play a key role in driving axon re-growth by forming aligned tubular guidance structures called bands of Büngner, which readily occurs in distal nerve segments as well as within autografts – currently the most reliable clinically-available bridging strategy. However, host Schwann cells generally fail to infiltrate large-gap acellular scaffolds, resulting in markedly inferior outcomes and motivating the development of next-generation bridging strategies capable of fully exploiting the inherent pro-regenerative capability of Schwann cells. We sought to create a preformed, implantable Schwann cell-laden microtissue that emulates the anisotropic structure and function of naturally-occurring bands of Büngner. Accordingly, we developed a biofabrication scheme leveraging biomaterial-induced self-assembly of dissociated rat primary Schwann cells into dense, fiber-like three-dimensional bundles of Schwann cells and extracellular matrix within hydrogel micro-columns. This engineered microtissue was found to be biomimetic of morphological and phenotypic features of endogenous bands of Büngner, and also demonstrated 8x and 2x faster rates of axonal extension in vitro from primary rat spinal motor neurons and dorsal root ganglion sensory neurons, respectively, compared to 3D matrix-only controls or planar Schwann cells. To our knowledge, this is the first report of accelerated motor axon outgrowth using aligned Schwann cell constructs. For translational considerations, this microtissue was also fabricated using human gingiva-derived Schwann cells as an easily accessible autologous cell source. These results demonstrate the first tissue-engineered bands of Büngner (TE-BoBs) comprised of dense three-dimensional bundles of longitudinally aligned Schwann cells that are readily scalable as implantable grafts to accelerate axon regeneration across long segmental nerve defects.